Aligning local government service delivery communication with digital citizen engagement: a case study of Makana Municipality - Machiri, Mwazvita Chipo (Rhodes University, Faculty of Commerce, Department of Information Systems, 2018)
The effective management of local municipalities in South Africa determines the quality of service delivery to citizens. Policies and other legislation have been implemented in an attempt to improve service delivery backlogs in South Africa since post-apartheid. However, these have not been effective in meeting community needs, hence leading to poor service delivery and increased community protests of frustration. These problems are partly linked to the lack of communication between government and citizens, and within internal government. Government needs to be held accountable for the services it provides, and improve on these services through practicing transparency, providing information to citizens, and allowing citizens to provide feedback on the various challenges experienced. Information access and communication is vital to the citizen engagement process, as this supports evidence-based engagement between citizens and government. Over the most recent years, innovative ICTs have emerged as a critical strategic tool in facilitating communication between the government and its citizens, commonly referred to as digital citizen engagement. The effective implementation of such initiatives at the local government level, especially in resource-constrained contexts, is not straightforward. This research aims to develop a guiding framework for aligning municipal communication processes with innovative ICTs to support ongoing social accountability and transparency through citizen engagement in local municipalities. The formulation of this framework is built on the Adaptive Structuration Theory, which is based on studying organisational change that occurs due to implementation and adoption of technology. Using a pragmatist approach and case study of Makana Municipality, the research study investigates a digital citizen engagement initiative called MobiSAM (Mobile Social Accountability Monitoring). The key findings from the qualitative empirical investigation indicates that there are significant social and political factors to consider when aligning Digital Citizen Engagement initiatives in a resource-constrained environment. The findings illustrated that the change and alignment process of DCE in local municipalities rely on a diverse set of inputs from different stakeholders, and a dynamic change process, which result in key citizen engagement outcomes of empowerment, accountability, transparency, and increased engagement depending "“ all depending on the success of the process. The extent of the outcomes will vary with the effectiveness of change management, idea generation, and participation, which Preliminaries are impacted by perceived usefulness, attitude towards the system, and the intentions of the user. The proposed framework provides a guideline for the implementation and introduction of innovations ICTs for citizen engagement at local government level.
Keywords: Political participation -- South Africa Makana; Municipal services -- South Africa Makana; Communication in public administration -- South Africa Makana; Internet in public administration -- South Africa Makana; Information technology -- South Africa Makana; Electronic government information -- South Africa Makana; Government accountability -- South Africa Makana